The developmental lipidome of Haemonchus contortus. Issue 12 (October 2018) - Wang, Tao; Nie, Shuai; Ma, Guangxu; Korhonen, Pasi K.; Koehler, Anson V.; Ang, Ching-Seng; Reid, Gavin E.; Williamson, Nicholas A.; Gasser, Robin B.
Graphical abstract: Highlights: The first global lipidome for a parasitic nematode – Haemonchus contortus . More than 500 lipid species (in 18 classes) were characterised with statistical confidence. Significant differences in lipid abundance in developmental transitions of H. contortus . Abstract: Lipids play crucial roles in the biology of organisms, particularly relating to cellular membranes, energy storage, and intra- or inter-cellular signalling. Despite the recent expansion of the lipidomics field, very little is known about the biology of lipids in metzoan pathogens, and, to date, there has been no global lipidomic study of a parasitic nematode. Using Haemonchus contortus (barber's pole worm) as a model, we describe the first known global lipidome for a parasitic nematode via high throughput LC–MS/MS-based lipidomics. We identified a total of 554 lipid species across four lipid categories, and 18 lipid classes exhibited alterations among six developmental stages (eggs; L3 and exsheathed L3 (xL3) and L4 larval stages; female and male adults) of H. contortus . The lipid composition and abundance of H. contortus changed significantly during the transition from free-living (egg, L3 and xL3) to parasitic (L4 and adult) stages. The three main changes observed were: (i) decreased synthesis of triradylglycerols; (ii) increased glycerophospholipids (predominantly glycerophosphoethanolamines and glycerophosphocholines); and (iii) a 'cooperative' modulation of ether-linked lipids and saturated fatty acids. These changes suggest specific adaptations, in terms of nutrient acquisition, metabolism and development, as the nematode makes its transition to the parasitic stage inside the host animal. This lipidomic data set serves as a stimulus for studies to understand lipid biology in parasitic worms, and their roles in parasite–host interactions and disease processes.